1995
DOI: 10.1111/j.1365-2621.1995.tb06215.x
|View full text |Cite
|
Sign up to set email alerts
|

Banana Shrimp, Penaeus merguiensis, Quality Changes During Iced and Frozen Storage

Abstract: Shelf life of banana shrimps, Penaeus merguiensis, were studied along with formaldehyde changes in their muscles during iced and frozen storage. K-value, timethylamine oxide nitrogen (TMAO-N), trimethylamine nitrogen (TMA-N), volatile basic nitrogen (VB-N) and sensory quality were determined. Shelf life was 4 days in ice, 6 days at -3°C and 9 wk at --10°C. They remained acceptable after 6 mo at -20°C. Formaldehyde was a good indicator in shrimp shelf life assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 24 publications
6
38
0
3
Order By: Relevance
“…A slight formation of black spot (score 1) was observed on shrimp packed in B after 4 th day, whereas no black spots were observed on shrimp packed in AwSUL, MAPwO 2 and MAPw/oO 2 after 4 days. Similar results were reported by Jiang & Lee [1988], Yamagata & Low [1995] and Goncalves et al [2003]. After 6 days, a slight darkening was observed in the head of shrimp packed in Aw-SUL, and Aw/oSUL (Figure 3).…”
Section: Sensory (Visual) Analysissupporting
confidence: 89%
“…A slight formation of black spot (score 1) was observed on shrimp packed in B after 4 th day, whereas no black spots were observed on shrimp packed in AwSUL, MAPwO 2 and MAPw/oO 2 after 4 days. Similar results were reported by Jiang & Lee [1988], Yamagata & Low [1995] and Goncalves et al [2003]. After 6 days, a slight darkening was observed in the head of shrimp packed in Aw-SUL, and Aw/oSUL (Figure 3).…”
Section: Sensory (Visual) Analysissupporting
confidence: 89%
“…The shelf life of prawns stored in air has long been known to be short (Al-Dagal and Bazaraa, 1999;Green, 1949;Haard, 1992), with Cobb (1976) stating that the shelf life of uncooked head-on shrimp was only 5 days. Yamagata and Low (1995), under similar conditions to the current trials, found that control cultured banana prawns killed immediately before storage had only 4-days shelf life at 0…”
Section: Introductionsupporting
confidence: 71%
“…• C. Yamagata and Low (1995), using similar conditions to the current trials, were only able to attain 4-days shelf life before blackening caused the rejection of control prawns. Treatment with sulphite (NaHSO 3 ) was only able to limit blackening to moderate levels after 6 days, with the prawns being rejected at this time due to this as well as deterioration of other sensory attributes.…”
Section: Demerit Assessment Of Prawns Within Packs At Openingmentioning
confidence: 60%
“…Karideslerde muhafaza sırasında bakteriler tarafından trimetilaminoksitin trimetilamine redüksiyonu, doku proteinlerinin dekompozisyonu ve deaminasyon gibi prosesler nedeniyle meydana gelen bazik aminler pH değerinde atışa neden olmaktadır 4 . Çeşitli araştırıcılar tarafından yapılan çalışmalarda 7.5-7.7 ve üzerinde pH değerine ulaşan karidesler bozuk olarak nitelendirilmiştir [25][26][27] .…”
Section: Tartişma Ve Sonuçunclassified
“…Dondurma, gıda maddelerinin korunmasında etkili bir yöntem olmasına rağmen, muhafaza sırasında dondurulmuş gıdaların kalitesinde kayıplar meydana gelmektedir. Rengin solması, yağların oksidasyonu, proteinlerin denatürasyonu, buzun sublimasyonu ve rekristalizasyonu dondurulmuş karideslerde görülen önemli kalite değişiklikleri olup bunlar dehidrasyona, ağırlık kaybına, kötü lezzete, acılaşmaya, sululuğun azalmasına, tekstürel değişikliklere, su bağlama kapasitesinin azalmasına, uçucu azotlu bileşenlerdeki artışa neden olmaktadır [3][4][5][6] . Kitosan, adından son yıllarda sıkça bahsedilen antimikrobiyel etkili bir polimerdir.…”
Section: Introductionunclassified